2018
DOI: 10.1680/jsuin.17.00069
|View full text |Cite
|
Sign up to set email alerts
|

Diamond-like carbon thin films prepared by pulsed-DC PE-CVD for biomedical applications

Abstract: In the present research, diamond-like carbon (DLC) thin films were applied on steel substrates by means of pulsed-direct current (DC) plasma-enhanced chemical vapor deposition (PE-CVD). The effects of bias voltage and deposition pressure on the films’ structure and properties were investigated. The Raman spectra of the films revealed features typical of G and D bands, indicating the formation of a DLC phase. The results demonstrate that the sp3 carbon fraction or the so-called diamond-like character of the DLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In the recent decades, several studies have shown the potential of using carbon-based nanomaterials, such as CNTs (Harrison and Atala, 2007; Touri et al, 2013; Sajid et al, 2016), graphene (Alasv and Mozafari, 2015; Chauhan et al, 2016; Khiabani et al, 2018), fullerene (Goodarzi et al, 2017), QDs (Lim et al, 2015), DLC (Wachesk et al, 2016; Derakhshandeh and Eshraghi, 2018a,b), MCNs (Kim et al, 2008), and CNFs (Yang et al, 2007) in various biomedical applications. The first reports on the Buckminsterfullerene (shortened to fullerene or buckyball) were the first attempts on innovative nano-carbons, leading an extraordinary explosion in universal research (Goodarzi et al, 2017).…”
Section: The Rise Of Carbon-family Nanomaterials: New Roles In Medicinementioning
confidence: 99%
“…In the recent decades, several studies have shown the potential of using carbon-based nanomaterials, such as CNTs (Harrison and Atala, 2007; Touri et al, 2013; Sajid et al, 2016), graphene (Alasv and Mozafari, 2015; Chauhan et al, 2016; Khiabani et al, 2018), fullerene (Goodarzi et al, 2017), QDs (Lim et al, 2015), DLC (Wachesk et al, 2016; Derakhshandeh and Eshraghi, 2018a,b), MCNs (Kim et al, 2008), and CNFs (Yang et al, 2007) in various biomedical applications. The first reports on the Buckminsterfullerene (shortened to fullerene or buckyball) were the first attempts on innovative nano-carbons, leading an extraordinary explosion in universal research (Goodarzi et al, 2017).…”
Section: The Rise Of Carbon-family Nanomaterials: New Roles In Medicinementioning
confidence: 99%
“…Derakhshandeh et al investigated the effects of bias voltage and deposition pressure in a pulsed-direct current (DC) plasmaenhanced chemical vapor deposition (PE-CVD) system on the structure and properties of the DLC coatings on stainless steel substrates. 7 The results reveal a positive effect of increasing bias voltage and a negative effect of increasing pressure on formation of sp 3 hybridized carbon (diamond-like) atoms over the sp 2 bonded carbons (graphite-like) in coatings. These operational variables also influenced internal stresses in the DLC coatings, which increased an order of magnitude for coatings produced with increasing bias voltage in this study.…”
Section: Ziqi Sunmentioning
confidence: 90%
“…Production of biodegradable nanofibers can be effective in generation of high performance scaffolds. On the other hand, doped PVA with various nanoparticle and other conductive materials developed a new class of materials with unique features and high application in many fields such as photocatalytic activity, anticorrosive, and hyperthermia . Therefore, modification of PVA is performed based on its application and properties.…”
Section: Introductionmentioning
confidence: 99%